1984
DOI: 10.1111/j.1600-0722.1984.tb00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion rate, buffer effect and number of lactobacilli and Streptococcus mutans of whole saliva of cigarette smokers and non‐smokers

Abstract: – Secretion rate and buffer effect of resting and stimulated whole saliva, and number of lactobacilli and S. mutans in stimulated whole saliva were determined for 182 subjects, of whom 109 were cigarette smokers. For secretion rate, no difference between smokers and non‐smokers was observed. The median buffer effect was significantly lower in smokers. The median numbers of lactobacilli and S. mutans were significantly higher in saliva of smokers. The number of lactobacilli was significantly correlated with nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
5
20
0
3
Order By: Relevance
“…The findings of the present study corroborate with much of the previous reports in the literature suggesting that smoking increases the growth of some cariogenic bacteria. Heintz (1984) and Sakkit and Knunttila (1996) reported independently that there is an increased S. mutans and lactobacillus count in smokers compared with nonsmokers. It should be mentioned that some studies have shown that smoking decreases some oral bacteria, especially Neisseria species (Marsh & Martin, 1999).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The findings of the present study corroborate with much of the previous reports in the literature suggesting that smoking increases the growth of some cariogenic bacteria. Heintz (1984) and Sakkit and Knunttila (1996) reported independently that there is an increased S. mutans and lactobacillus count in smokers compared with nonsmokers. It should be mentioned that some studies have shown that smoking decreases some oral bacteria, especially Neisseria species (Marsh & Martin, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Some research indicated that smoking increases the growth of oral bacteria (Heintz, 1984;Vaananen et al, 1994), while others reported opposite findings (Ertel, Eng, & Smith, 1991;Marsh & Martin, 1999). Those authors who believed in the booster effect of smoking on the growth of S. mutans concluded that smoking increases the risk of dental caries (Lindemeyer, Baum, Hsu, & Going, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, Voelker et al showed that there is a significant relationship between smoking, a decreased pH of stimulated saliva as well as its buffering capability, and an increased risk of caries, where smoking has no effect on the Streptococcus mutans bacteria (main cavity-forming bacteria) (23). On the other hand, Heintze et al showed that the number of lactobacillus and S. mutans are higher in smokers’ saliva than non-smokers (24). Different studies have introduced smoking as a cause for tooth loss (17, 18, 25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has immunological and bacteriostatic properties [35, 36]. Heintze [37] demonstrated that for cigarette smokers, the buffering capacity of saliva was substantially lower than nonsmokers and that the number of Lactobacilli and Streptococcus mutans was significantly higher in saliva of smokers than nonsmokers. The decrease in the buffering capacity of saliva and increase in the level of cariogenic bacteria result in high incidence of caries in smokers, which eventually leads to tooth loss.…”
Section: Discussionmentioning
confidence: 99%